Novel benzothiazole based sulfonylureas/sulfonylthioureas: design, synthesis and evaluation of their antidiabetic potential. (10th June 2016) - Kharbanda, Chetna; Alam, Mohammad Sarwar; Hamid, Hinna; Javed, Kalim; Bano, Sameena; Ali, Yakub; Dhulap, Abhijeet; Alam, Parwez; Pasha, M. A. Q.
Abstract : Twenty-eight benzothiazole based sulfonylureas/sulfonylthioureas were synthesized and were found to be effective against diabetes as PPAR-γ agonists. Abstract : In the present study, twenty-eight benzothiazole based sulfonylureas/sulfonylthioureas were synthesized and were assessed for their antidiabetic effect in a normoglycemic rat model by the in vivo oral glucose tolerance test (OGTT). All the synthesized compounds were studied for their interactions inside the PPAR-γ receptor site through a docking study. Subsequently, in vitro PPAR-γ transactivation assay was performed on ten active compounds7c, 7d, 7i–l, 8c, 8d, 8g, and8h which showed potent antidiabetic activity in the OGTT (better than standard drugs) and also showed a good dock score with the PPAR-γ receptor site. These active ten compounds were also found to transactivate PPAR and therefore were assessed for their antidiabetic potential on the STZ induced diabetic model. Effects of these compounds on body weight were also monitored during the course of study. Furthermore, the most effective compound7j was evaluated for its effect on PPAR-γ gene expression.